Development of Ag/AgX (X = Cl, I) nanoparticles toward antimicrobial, UV-protected and self-cleanable viscose fibers. (1st October 2018) - Rehan, Mohamed; Khattab, Tawfik A.; Barohum, Ahmed; Gätjen, Linda; Wilken, Ralph
Graphical abstract: Highlights: Multi-functionalization of viscose fibers was achieved by in-situ synthesis of Ag/AgX (X = Cl, I). Ag/AgX/viscose fibers were prepared under ultrasonic and UV irradiation. Ag/AgX/viscose fibers exhibit good antimicrobial and UV protection. Ag/AgX/viscose fibers exhibit good photocatalytic properties under visible light. Abstract: In situ synthesis of Ag/AgX nanoparticles (NPs) onto viscose fibers adds new functionalities and broadens their applications. In this study, Ag/AgX (X = Cl, I) NPs were in situ synthesized onto viscose fibers to impart brilliant colors, UV-protection, antimicrobial, self-cleaning, and photocatalytic properties. The AgX NPs were deposited on the fibers by ultrasonic irradiation, while Ag-NPs were formed by photoreduction of excess Ag + ions under UV irradiation. The Ag/AgX NPs-loaded onto viscose fibers endowed with pale yellow for Ag/AgI and pale purple/violet for Ag/AgCl. The colored viscose fibers showed excellent antimicrobial activity against Escherichia coli (gram-negative), Staphylococcus aureus (Gram positive), and Candida Albican . The Ag/AgX/viscose fiber also showed excellent photocatalytic and self-cleaning activity toward degradation of methylene blue.